Literature review on industrial digital platforms : A business model perspective and suggestions for future research - Madanaguli, Arun; Parida, Vinit; Sjödin, David; Oghazi, Pejvak (Elsevier, 2023)
Rapid digitalization of industries has led to the proliferation of complex industrial digital platforms; however, few industrial platform leaders have successfully established sustainable business models around their offerings. The need for a concrete definition of industrial digital platforms and their business models further complicates our understanding of the issue. In this prospecting review, we critically analyze the existing literature on industrial digital platforms to identify key research themes and research gaps and propose a future research agenda for the industrial digital platform literature from a business model perspective. Drawing on insights from research on industrial platforms, digitalization, digital servitization, and business-to-business (B2B) relationships, our analysis focuses on three key themes in defining the boundaries of industrial digital platforms and the crucial aspects of value creation, value delivery, and value capture on such platforms: (a) co-creative value creation, (b) digitally integrated value delivery, and (c) mutual value capture. The findings of this study and a future research agenda framework provide a roadmap for advancing the understanding of business models for industrial digital platforms. This research aims to contribute to the emerging field of industrial digital platforms and guide future research endeavors in this domain, unlocking the full potential of these platforms for businesses and industries.
Keywords: B2B; Generativity; Capabilities; Industrial platform; Platform ecosystem; Digital platform; Ecosystem; Digital servitization; Co-creation; business models; fi=Strateginen johtaminen|en=Strategic Management|